Political activists are not driven by instrumental motives: Evidence from two natural field experiments - Anselm Hager; Lukas Hensel; Johannes Hermle; Christopher Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Are political activists driven by instrumental motives such as making a career in politics or mobilizing voters? We implement two natural field experiments in which party activists are randomly informed that canvassing is i) effective at mobilizing voters, or ii) effective for enhancing activists' political careers. We find no effect of the treatments on activists' intended and actual canvassing behavior. The null finding holds despite a successful manipulation check and replication study, high statistical power, a natural field setting, and an unobtrusive measurement strategy. Using an expert survey, we show that the null finding shifted Bayesian posterior beliefs about the treatment's effectiveness toward zero. The evidence thus casts doubt on two popular hypothesized instrumental drivers of political activism - voter persuasion and career concerns - and points toward expressive benefits as more plausible motives.
Keywords: 330